The feeling body : affective science meets the enactive mind - Colombetti, Giovanna (MIT Press, 2013)
In The Feeling Body, Giovanna Colombetti takes ideas from the enactive approach developed over the last twenty years in cognitive science and philosophy of mind and applies them for the first time to affective science -- the study of emotions, moods, and feelings. She argues that enactivism entails a view of cognition as not just embodied but also intrinsically affective, and she elaborates on the implications of this claim for the study of emotion in psychology and neuroscience. In the course of her discussion, Colombetti focuses on long-debated issues in affective science, including the notion of basic emotions, the nature of appraisal and its relationship to bodily arousal, the place of bodily feelings in emotion experience, the neurophysiological study of emotion experience, and the bodily nature of our encounters with others. Drawing on enactivist tools such as dynamical systems theory, the notion of the lived body, neurophenomenology, and phenomenological accounts of empathy, Colombetti advances a novel approach to these traditional issues that does justice to their complexity. Doing so, she also expands the enactive approach into a further domain of inquiry, one that has more generally been neglected by the embodied-embedded approach in the philosophy of cognitive science.